Kidney transplantation analysis in a service performing other abdominal organs transplantation - Kataiama, Andreia Midori Matuoka; Ianhez, Luiz Estevan; Perosa, Marcelo; Mota, Leonardo Toledo; Branez, Juan Rafael; Azevedo, Rodrigo; Noujain, Huda Maria; Moreno, Marcio; Genzini, Tercio; Castro, Marcos (Brazilian Journal of Transplantation, 2013)
Purpose: To analyze the experience with renal transplantation in an abdominal organ transplantation service performed by a multidisciplinary team of kidney, pancreatic and liver transplantation. Methods: Between December/2010 to December/2012, 72 kidney transplants were performed by the Hepato staff from Hospital Bandeirantes, analyzed in June/2013. Results: As to the demographics, mean age was 40 years (19-69 years), and 50% of patients presented diabetes mellitus, 6.94% were kidney transplant recipients after liver transplantation, and the remaining patients had nephrosclerosis, glomerulonephritis, polycystic kidney disease, idiopathic causes, among others. As to the immunosuppressant, it was used tacrolimus, mycophenolate sodium, and prednisone thymoglobulina (the latter used in only two cases) from living donors in 85% of cases. Surgical complications were low: a case of urinary fistula, a hematoma, five lymphocele and an incision dehiscence; no graft was lost by surgical complication. The most common clinical complications were urinary tract infection and CMV with 13.9% each, acute cellular rejection in 11.1%, post-transplant diabetes in 8.3%, and 4.2% polyomavirus. There was loss of two grafts: one by chronic rejection and death from stroke. The mean serum creatinine in the final assessment was 1.2 mg / dL. Conclusion: Results demonstrated in this work presented a high-risk for co- morbidities in patients such as diabetic and pre and post TOSNR pancreas transplant patients (non-renal solid organ transplantations.